Relative Contributions of Intracranial Pressure and Intraocular Pressure on Lamina Cribrosa Behavior. (17th March 2019) - Tong, Junfei; Ghate, Deepta; Kedar, Sachin; Gu, Linxia
Abstract : Purpose . To characterize the relative contributions of intraocular pressure (IOP) and intracranial pressure (ICP) on lamina cribrosa (LC) behavior, specifically LC depth (LCD) and LC peak strain. Methods . An axially symmetric finite element model of the posterior eye was constructed with an elongated optic nerve and retro-orbital subarachnoid space ensheathed by pia and dura mater. The mechanical environment in LC was evaluated with ICP ranging from 5 to 15 mmHg and IOP from 10 to 45 mmHg. LCD and LC peak strains at various ICP and IOP levels were estimated using full factorial experiments. Multiple linear regression analyses were then applied to estimate LCD and LC peak strain using ICP and IOP as independent variables. Results . Both increased ICP and decreased IOP led to a smaller LCD and LC peak strain. The regression correlation coefficient for LCD was −1.047 for ICP and 1.049 for IOP, and the ratio of the two regression coefficients was −1.0. The regression correlation coefficient for LC peak strain was −0.025 for ICP and 0.106 for IOP, and the ratio of the two regression coefficients was −0.24. A stiffer sclera increased LCD but decreased LC peak strain; besides, it increased the relative contribution of ICP on the LCD but decreased that on the LC peak strain. Conclusions . ICP and IOP have opposing effects on LCD and LC peak strain. While their effects on LCD are equivalent, the effect of IOP on LC peak strain is 3 times larger than that of ICP. The influences of these pressure are dependent on sclera material properties, which might explain the pathogenesis of ocular hypertension and normal-tension glaucoma.